ANALYSIS ON INTERACTIONS RELEVANCE AMONG COGNITIVES STRATEGIES AND PROCESSING MODALITY - Luna Blanco, Rafael (Anales de Psicología / Annals of Psychology, 2000)
Among the different approaches to study visual perception, one of them has focussed on the differentiation about two important levels: the global or holistic processing vs local or analytic processing and, therefore, many studies have analysed the influence of several stimular variables and their respective interactions. Into the same frame, the aim of this work has been to study the influence of several subject variables, such as the processing strategies (in relation to cognitive style) and types of processing (in relation to hemispheric specialization) in front of different stimular conditions. The results have shown an interaction between "Stimulus structure" x "Visual field" according to discoveries from preceding researches and between "Stimulus structure" x "Cognitive style", which suggests the use of different strategies depending on the cognitive style as it looks like to derive changing the results pattern in the presence of task demanding with different stimulus structures.